Orientation and the search for meaning - Pavoncello, Daniela (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
In this contribution we want to highlight, both from a systemic - interactionist, constructivist and above all logotherapeutic - point of view, according to V. Frankl's model, the relevance of the sense-seeking perspective in orientation activities, especially addressed to young people living in marginalised conditions, also as a tool for preventing discomfort. Recent studies have shown that certain constructs, such as optimism, hope and the search for meaning, promote a positive time perspective. Therefore, it will be necessary to rethink orientation, in an educational key, by virtue of the development of these competences.